Financial exposure and bank mergers: Micro and macro evidence from the EU - Laura Lebastard (European Central Bank (ECB), 2022)
This paper studies for the first time the links between interbank liability and equity markets (financial exposure), and mergers and acquisitions (M&As) in the European banking sector, both at the micro and macro level. Using a binary logit model, the paper first examines - at the micro level - how financial exposures between banks affect the probability of M&A. It finds that financial interlinkages significantly increase the chances of them taking place. Using a gravity model, the paper then investigates - at the macro level - whether the micro results hold. Not only do financial links are positively and significantly correlated with the number of M&As between countries, but they are also a better predictor than trade - traditionally used in the macro literature on M&A. Since the Capital Market Union would help to geographically diversify banks' portfolio, it would therefore also foster cross-border M&As. Finally, the paper builds a M&A compatibility index for each pair of EU countries. The study highlights strong M&As prospects linked to high financial interlinkages in core Europe, which could be the sign of a future asymmetrical financial integration in the EU.
Keywords: G21; G34; F21; F34; F36; 330; Bank consolidation; financial exposure; logit model; gravity model